2018
DOI: 10.1073/pnas.1714790115
|View full text |Cite
|
Sign up to set email alerts
|

Superresolution imaging of individual replication forks reveals unexpected prodrug resistance mechanism

Abstract: Many drugs require extensive metabolism en route to their targets. High-resolution visualization of prodrug metabolism should therefore utilize analogs containing a small modification that does not interfere with its metabolism or mode of action. In addition to serving as mechanistic probes, such analogs provide candidates for theranostics when applied in both therapeutic and diagnostic modalities. Here a traceable mimic of the widely used anticancer prodrug cytarabine (ara-C) was generated by converting a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 64 publications
7
33
1
Order By: Relevance
“…S1a) revealed a punctate distribution as well as changing physical morphology across S-phase ( Fig. 1a), similar to previous observations using immuno-gold electron microscopy 26 , conventional optical microscopy 16,27 and different super-resolution microscopy 21,[28][29][30][31] . However, the superior spatial resolution afforded by STORM (~20 nm) enabled us to perform more accurate quantitative characterization of RFi, particularly for findings based on multi-color colocalization analysis.…”
Section: Super-resolution Imaging and Quantitative Characterization Osupporting
confidence: 89%
“…S1a) revealed a punctate distribution as well as changing physical morphology across S-phase ( Fig. 1a), similar to previous observations using immuno-gold electron microscopy 26 , conventional optical microscopy 16,27 and different super-resolution microscopy 21,[28][29][30][31] . However, the superior spatial resolution afforded by STORM (~20 nm) enabled us to perform more accurate quantitative characterization of RFi, particularly for findings based on multi-color colocalization analysis.…”
Section: Super-resolution Imaging and Quantitative Characterization Osupporting
confidence: 89%
“…This median value and size heterogeneity are very similar to what has been attributed in earlier studies to the replication domains in human cells using optical super-resolution ( 16 ) and electron microscopy ( 15 ). In eukaryotes, very recent studies have suggested that on average these replication units of 150 nm correspond to the sites of DNA replication with four co-replicating DNA segments of approximately 20 kb ( 18 , 58 ). As H. volcanii replication origins are separated by several hundreds of kilobases ( 24 ), we find it unlikely that several clustered cis -acting replication origins would be simultaneously processed.…”
Section: Discussionmentioning
confidence: 99%
“…They conrmed the equal biological prole of AzC in cell culture and in vivo as ara-C. Further studies of the AzC with classical azide-alkyne click chemistry, including the gSTED imaging experiment, allowed them to understand the contradiction of cell-type selectivity of nucleoside-based drugs. 65…”
Section: Clickable Drug Surrogatesmentioning
confidence: 99%